lncRNA TINCR sponges miR-214-5p to upregulate ROCK1 in hepatocellular carcinoma - Min Hu; Yaowu Han; Ying Zhang; Yuanfeng Zhou; Lin Ye (BMC, 2020)
Abstract Background Our preliminary bioinformatics analysis showed that lncRNA TINCR may absorb miR-214-5p by serving is sponge, while miR-214-5p targets ROCK1. This study aimed to investigate the interactions among these 3 factors in hepatocellular carcinoma (HCC). Methods Expression of TINCR, ROCK1 and miR-214-5p in HCC and non-tumor tissues was detected by performing qPCR. The correlations among TINCR, ROCK1 and miR-214-5p in HCC tissues were analyzed by performing linear regression. Overexpression experiments were performed to analyze gene interactions. Cell proliferation was analyzed by CCK-8 assay. Results We found that TINCR and ROCK1 were upregulated, while miR-214-5p was downregulated in HCC. TINCR and ROCK1 were positively correlated, while TINCR and miR-214-5p were not significantly correlated. In HCC cells, TINCR overexpression is followed by ROCK1 overexpression, while miR-214-5p overexpression induced the downregulation of ROCK1. In addition, TINCR and miR-214-5p did not affect the expression of each other. TINCR and ROCK1 overexpression led to increased rate of cancer cell proliferation, while miR-214-5p played an opposite role and reduced the effects of TINCR overexpression. Therefore, TINCR sponges miR-214-5p to upregulate ROCK1 in HCC, thereby promoting cancer cell invasion and migration.